A Pretest to Differentiate Between Weak and Nearly-Weak Instrument Asymptotics - Mehmet Caner (International Econometric Review (IER), 2011)
We propose a pretest, bootstrap Kolmogorov-Smirnov test, to differentiate between weak and nearly-weak asymptotics. This is based on bootstrapping Wald Continuous Updating Estimator (CUE) based test. Since Wald CUE test has different limits under weak and nearly-weak cases this can be used in a pretest. We also conduct some simulations and show that some of the asset pricing models conform to nearly-weak asymptotics.
Keywords: C11; C20; C30; 330; Bootstrap; Kolmogorov-Smirnov Test